Authority Of The Village Head In Transfer Of Rights To Traditional Land Law Perspective Land Registration - Suyanto (IHSA Institute, 2022)
The Village Head as the lowest government apparatus has very strategic tasks in assisting the Head of the Land Office in carrying out land registration including the making of land sale and purchase deeds in accordance with applicable laws and regulations. The procedure for the sale and purchase of land rights has been determined according to the applicable provisions, namely Law Number 5 of 1960 concerning Basic Regulations on Agrarian Principles. The transfer of title to land that is not yet certified as buying and selling land must be proven by a deed drawn up by and in front of the official deed of land deed or PPAT. To guarantee legal certainty in the sale and purchase of land can only be done on land owned based on land rights, meaning that the object of land is validated with proof of ownership of land rights in the form of a certificate. Therefore, the task of the Village Head is expected to be a motivator for the community who hold land rights so that they have the awareness to buy and sell land in front of the PPAT rather than in front of the Village Head, because until now there are no regulations governing strict sanctions against the village head in exercising his authority regarding the transfer of rights.